2015
DOI: 10.1016/j.engstruct.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of peak displacements in steel structures through dimensional analysis and the efficiency of alternative ground-motion time and length scales

Abstract: This paper deals with the estimation of maximum displacements in single-degree-of-freedom (SDOF) systems simulating typical steel structures by means of dimensional analysis. Peak deformation demands in bilinear systems (representative of moment resisting frames) are considered as well as additional pinching models depicting partially-restrained (PR) and concentrically-braced (CB) frames subjected to a series of non-coherent acceleration records. Particular attention is given to the identification of efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Engineers and seismologists have employed a range of amplitude, energy, averaged frequency content, duration and envelope shape measures etc. (Málaga-Chuquitaype 2015, Sarieddine and Lin 2013, Cornell 1997, Hancock and Bommer 2007, Iervolino et al 2006, Raghunandan and Liel 2013, Kramer 1996 to attempt to capture the most significant factors that govern the nonlinear response of the system. In particular, if we consider near/far field, with/without pulses, time-series it is immediately apparent that there are differences.…”
Section: Introductionmentioning
confidence: 99%
“…Engineers and seismologists have employed a range of amplitude, energy, averaged frequency content, duration and envelope shape measures etc. (Málaga-Chuquitaype 2015, Sarieddine and Lin 2013, Cornell 1997, Hancock and Bommer 2007, Iervolino et al 2006, Raghunandan and Liel 2013, Kramer 1996 to attempt to capture the most significant factors that govern the nonlinear response of the system. In particular, if we consider near/far field, with/without pulses, time-series it is immediately apparent that there are differences.…”
Section: Introductionmentioning
confidence: 99%
“…By expressing the displacement response of rigid-plastic, elastoplastic and bilinear single-degreeof-freedom (SDOF) systems in dimensionless -terms, they showed that dimensionless deformations become independent of the intensity of the ground-motion and follow a single 'master curve'. Dimensional analysis has also been applied for assessing the displacement response of SDOF structures simulating multi-storey moment resisting steel frames subjected to pulse-like ground-motions (Karavasilis et al 2010), to the analysis of the earthquake-induced pounding between adjacent structures (Dimitrakopoulos et al 2009b) and, more recently, to structures representing moment-resisting, partially-restrained, and concentrically-braced frames under real non-pulselike earthquake actions (Málaga-Chuquitaype 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While pulse-type excitations have the advantage of possessing clear time and length metrics (Vassiliou and Makris 2011), the implementation of dimensional analysis for noncoherent earthquake action involves the challenge of selecting an adequate set of groundmotion time and length scales (Dimitrakopoulos et al 2009a;Málaga-Chuquitaype 2015). Although a comprehensive investigation on the merits of different time and length scale was carried out in Málaga-Chuquitaype (2015), their study, like the vast majority of prior research, focused on dimensionless deformation demands while dimensionless floor acceleration response remains largely unexplored. An investigation on the relevant literature yielded only one article related to the dimensional analysis of peak floor accelerations, in the context of investigating the effect of pounding on the seismic response of adjacent multi-degree-of-freedom (MDOF) buildings (Zhai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Additionally, numerous studies have approached the problem of estimation of inelastic drifts by analysing SDOF oscillators. [4][5][6][7][8][9][10][11] The main parameters identified in these studies as governing for the inelastic response of SDOF systems include the initial elastic period, the post-yield stiffness, the hysteretic constitutive law, and the frequency content of the input ground motion. The simple models used in these studies inherently cannot consider phenomena such as highermode effects and variations in distribution of strength and stiffness.…”
Section: Introductionmentioning
confidence: 99%